Policy Literacy and Farmer Capacity as Determinants of Corn Productivity: An Educational Governance Perspective from Gorontalo - Merita Ayu Indrianti; Dewa Oka Suparwata; Moh. Muchlis Djibran; Nurlia Ripo (Journal of General Education and Humanities, 2026)
The digitalization of agricultural governance in Indonesia has created new challenges in the implementation of fertilizer subsidy policies, particularly for farmers with limited technological capacity. This study aims to analyze the influence of socio-digital literacy, administrative accessibility, and intergenerational support on corn productivity in the Gorontalo Regional Hub following the implementation of Presidential Regulation No. 6 of 2025. The study also examines the relative contribution of policy literacy compared to conventional governance factors in supporting food sovereignty outcomes. This research employed a Sequential Explanatory Mixed-Methods design involving quantitative and qualitative approaches. Quantitative data were collected from 150 corn farmers in the Limboto and Limboto Barat Districts using structured questionnaires, while qualitative data were collected through interviews with policymakers, extension coordinators, and youth intermediaries. Data analysis included descriptive statistics, thematic analysis, and Prospective Structural Analysis using the MICMAC method to identify key systemic variables. The results indicate that socio-digital literacy (LITE_X4) was one of the most influential variables in the governance system, with an influence score of 264 in the MICMAC analysis. Intergenerational support recorded the highest governance score (4.51), while the spatial-digital synchronization variable (P11) showed the lowest score (3.14), indicating persistent administrative barriers in the digital subsidy system. The findings also revealed a positive association between understanding of digital policy and productivity outcomes (r = 0.397, p < 0.01), although the study does not claim direct causation. Qualitative findings showed that youth intermediaries played an important role in helping senior farmers navigate digital administrative systems. This study concludes that digital literacy and administrative accessibility are important components of contemporary agricultural governance. The findings suggest the need for more adaptive digital governance models, participatory extension services, and inclusive policy mechanisms to reduce administrative exclusion in agricultural subsidy systems.